PENGEMBANGAN APLIKASI WEB UNTUK MONITORING REKAM MEDIS PADA SISTEM E-HEALTH TRACKER BERBASIS IOT - Martogi Jekson C. Siagian; Geraldo Alvin Sugiarto; I Gusti Agung Putu Raka Agung; Gede Sukadarmika (Program Studi Teknik Elektro UNUD, 2025)
The digital transformation in the healthcare sector continues to advance significantly, particularly in the recording and management of electronic medical records. This study proposes the development of a web-based application for monitoring medical records within an E-Health Tracker system that leverages the Internet of Things (IoT), designed using a User-Centered Design (UCD) approach. The system aims to provide seamless access to health information for users through an intuitive interface and cross-device compatibility. The integration of IoT devices enables the transmission of vital health indicators—such as heart rate, body temperature, and oxygen levels—to a central server, which are then visualized through a web-based platform. A key advantage of this application lies in its flexible access and its potential to bridge gaps in healthcare services, especially in regions with limited medical infrastructure. This research is expected to contribute meaningfully to the equitable distribution of healthcare access and to raise public awareness of health literacy through the implementation of IoT-integrated web technologies.